Assessment of Livelihood Security and Constraints Encountered bBy Small and Marginal Cotton Growers - D. Manikanta,; Satpathy, Bineeta (Indian Journal of Extension Education, 2023)
The study examines the constraints faced by cotton growers in achieving livelihood security in the Guntur district of Andhra Pradesh, India. The investigation used a Livelihood Security (LS) index comprising seven elements, including food security, economic security, health security, educational security, social security, institutional security, and infrastructural security. Data were collected from 120 cotton farmers using structured interviews, and statistical analysis was employed to assess the level of livelihood security and identify constraints. The findings indicate that a substantial proportion of farmers have medium to high levels of livelihood security, but certain challenges persist. Among the constraints, lack of knowledge of technical skills and relevant technologies, low market prices for products and inadequate knowledge of marketing stand out as significant obstacles. Addressing these challenges can contribute to enhancing the overall well-being and livelihood security of cotton growers in the region.